A systems change intervention for nurse-led smoking cessation care in hospitals. Issue 2 (April 2019) - Malone, Victoria; Ezard, Nadine; Clifford, Brendan; Middleton, Sandy; McInnes, Elizabeth; Bonevski, Billie
Abstract: Aim: The aim of this study was to determine the feasibility and acceptability of a systems change intervention on nurses' inpatient management of tobacco dependence. Methods: A mixed methods study involving an uncontrolled pre and post study design and qualitative methods. The systems change intervention consisted of: tobacco use questions within the routine nursing care admission assessment forms; provision of nicotine replacement therapy (NRT) as a 'nurse-initiated' medication; and nurse education. A medical record audit was conducted 4 months before and 1 month after implementation to assess recording of: smoking status, offer of NRT and referral to a telephone tobacco cessation counselling service 'Quitline'. Focus groups and semi-structured interviews were conducted to ascertain acceptability of the systems change intervention. Chi square analysis compared identification of inpatients' who smoke and offer of NRT pre and post implementation. Constant comparative analysis was used to analyse qualitative data. Findings: Nurse recording of inpatient smoking status (83% to 90%) did not significantly improve. However offer of nurse-initiated NRT significantly increased from 0% to 34% (p = 0.02). Acceptance of NRT increased from 50% to 64% (p = 0.055) and offer of referral to Quitline increased (0% to 4%) but increases were not significantly different. Three themes emerged from the qualitative data: Education for the nurses, nurse leadership and therapeutic alliance. Conclusion: The study results show promise as our intervention increased nurses' offer of NRT for inpatients' who smoked. New approaches need to be developed to support patients who do not want to or are not ready to quit.